HELICOBACTER PYLORI AND t(11;18)(q21;q21) TRANSLOCATION IN GASTRIC MALT LYMPHOMA - LIMA,Karine Sampaio (2014)
ContextGastric mucosa-associated lymphoid tissue (MALT) lymphoma is clearly associated with Helicobacter pylori gastritis and can be cured with anti- H pylori therapy alone. The presence of t(11;18)(q21;q21) translocation is thought to predict a lower response rate to anti- H pylori treatment.ObjectivesTo study the presence of t(11;18)(q21;q21) genetic translocation and its clinical impact in low-grade gastric MALT lymphoma Brazilian patients.MethodsA consecutive series of eight patients with gastric MALT lymphoma were submitted to gastroscopy, endoscopic ultrasound, histopathological examination, H pylori search and RT-PCR-based methodology. All patients received anti-H pylori treatment. Eradicated patients were followed-up every 3-6 months for 2 years.ResultsEight patients were studied. All patients had tumor involvement restricted to the mucosa or submucosa and seven patients had low-grade gastric MALT lymphoma. All infected patients achieved H pylori eradication. Histological tumor regression was observed in 5/7 (71%) of the low-grade gastric MALT lymphoma patients. The presence of t(11;18)(q21;q21) translocation was found in 4 (57%) of these patients; among them only two had histological tumor regression following H pylori eradication.ConclusionsRT-PCR is a feasible and efficient method to detect t(11;18)(q21;q21) translocation, being carried out in routine molecular biology laboratories. The early detection of such translocation can be very helpful for better targeting the therapy to be applied to gastric MALT lymphoma patients.